Handbook of research on effective electronic gaming in education - Ferdig, Richard E. (Richard Eugene) (Information Science Reference, 2009)
"This book presents a framework for understanding games for educational purposes while providing a broader sense of current related research. This creative and advanced title is a must-have for those interested in expanding their knowledge of this exciting field of electronic gaming"--Provided by publisher.